The dynamic of macroeconomics elements in Malaysia: further insight into causality analysis / Dayang Hummida Abang Abdul Rahman … [et al.] - Abang Abdul Rahman, Dayang Hummida; Majidi, Nuzaihan; Kasuma, Jati; Yacob, Yusman; Awang Marikan, Dayang Affizzah (Universiti Teknologi Mara, Selangor: Puncak Alam Campus, 2019)
This paper intends to explore the causality effect between Growth Domestic Product (GDP), population and unemployment in Malaysia. Based on the observation of Malaysia’s historical data, there is a distinct movement in each of these individual macroeconomics components over the years. Past literature within the same area has illustrated various patterns on the possibility of a causal relationship that each variable has on one another. Several stages of analysis are conducted to verify the presence of causality effect from Malaysian economic perspective, which includes unit root test that employs the Augmented Dickey Fuller (ADF), Phillips-Perron (PP) and Kwiatkowski-Phillips-Schmidt-Shin (KPSS) procedures, followed by Johansen and Juselius test of cointegration and Granger-causality test based on Vector Error Correction Model (VECM) using E-views software. Each procedure is conducted using Malaysia’s time series data for each of the three elements from 1980 to 2013 obtained from Malaysia’s Department of Statistics. Our findings revealed that there is one cointegration detected for the tested variables; whereas the results indicate that population can Granger cause unemployment in the short run. Furthermore, it is found that unemployment solely bears the effect from short run adjustment to bring about the long run equilibrium within the tested framework. This study is important for the policy maker to understand the reason behind the causality effect that could jeopardize the rate of unemployment in Malaysia. As the attention is given specifically to three variables particularly GDP, population and unemployment, this study is aimed at broadening the prospect for further investigation within the same area of macroeconomics.